Introduction (French version) (Signifiances (Signifying), 2021)
In this issue of Signifiances (Signifiyng) we will focus on a theoretical and dynamic point of view on the linguistic and semiotic dimensions at work in the constitution of individual and collective experience. The aim is to investigate the hypothesis of constitutive compatibility between two fundamental characteristics of meaning, namely its perceptibility and its sociality. These characteristics will be re-seized from the perspective of semiotic anthropology with a phenomenological, expressivist, and morphodynamic vocation. It is a perspective that is interested, at first sight, in the formation of the planes of expression which mediate the inscription and engagement of the subjects within social life. Thus, the various contributions will discuss a theoretical framework that encompasses what is called semiogenetic, which makes it possible to clarify the specific semiotic and semiolinguistic forms and issues that are imposed on the actors and constantly redirect their attention.